2020
DOI: 10.1186/s12905-020-00966-y
|View full text |Cite
|
Sign up to set email alerts
|

General and reproductive health outcomes among female greenhouse workers: a comparative study

Abstract: Background: Agricultural activities as well as exposure to pesticides could have many adverse effects on health status and reproductive outcomes especially in reproductive aged greenhouse workers. The present study aimed to compare the general and reproductive health outcomes between female greenhouse workers and housewives. Methods: This cross-sectional study was conducted on 645 females of reproductive age. They were categorized into two groups according to occupation in greenhouse (308 female greenhouse wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 36 publications
1
20
0
4
Order By: Relevance
“…The significantly higher number of PN born by mothers with a rural residence detected in our study is in concordance with previous studies [26][27][28][29]. The origin of such an association may lie in the fact that many pesticides, most likely also used in the rural areas from which the mothers came, are endocrine disruptors with a wide range of effects on oestrogen and androgen receptors and aromatase [30].…”
Section: Discussionsupporting
confidence: 92%
“…The significantly higher number of PN born by mothers with a rural residence detected in our study is in concordance with previous studies [26][27][28][29]. The origin of such an association may lie in the fact that many pesticides, most likely also used in the rural areas from which the mothers came, are endocrine disruptors with a wide range of effects on oestrogen and androgen receptors and aromatase [30].…”
Section: Discussionsupporting
confidence: 92%
“…Rahimi et al interviewed women working in greenhouses and married for at least one year, with 338 unexposed controls from nearby villages, in a cross-sectional study from southern Iran [44]. The women were 16-49 years of age.…”
Section: Spontaneous Fetal Loss (Miscarriage)mentioning
confidence: 99%
“…Numerous studies have shown that occupational exposure or residence near agricultural environments where pesticides are frequently used confers a higher risk of adverse reproductive health outcomes (Shirangi et al 2008 ; Naidoo et al 2011 ; Razi et al 2016 ; Settimi et al 2008 ; Rahimi et al 2020 ). In the few studies that found no such association (Bell et al 2001 ; Willis et al 1993 ), dietary zinc intake might not have been considered.…”
Section: Discussionmentioning
confidence: 99%